High light intensity aggravates latent manganese deficiency in maize. (1st August 2020) - Long, Lizhi; Pedas, Pai R; Kristensen, Rebekka K; Schulze, Waltraud X; Husted, Søren; Zhang, Guoping; Schjoerring, Jan K; Yuan, Lixing
Abstract: Manganese (Mn) plays an important role in the oxygen-evolving complex, where energy from light absorption is used for water splitting. Although changes in light intensity and Mn status can interfere with the functionality of the photosynthetic apparatus, the interaction between these two factors and the underlying mechanisms remain largely unknown. Here, maize seedlings were grown hydroponically and exposed to two different light intensities under Mn-sufficient or -deficient conditions. No visual Mn deficiency symptoms appeared even though the foliar Mn concentration in the Mn-deficient treatments was reduced to 2 µg g –1 . However, the maximum quantum yield efficiency of PSII and the net photosynthetic rate declined significantly, indicating latent Mn deficiency. The reduction in photosynthetic performance by Mn depletion was further aggravated when plants were exposed to high light intensity. Integrated transcriptomic and proteomic analyses showed that a considerable number of genes encoding proteins in the photosynthetic apparatus were only suppressed by a combination of Mn deficiency and high light, thus indicating interactions between changes in Mn nutritional status and light intensity. We conclude that high light intensity aggravates latent Mn deficiency in maize by interfering with the abundance of PSII proteins. Abstract : High light intensity affects the abundance of PSII proteins in the photosynthetic apparatus and aggravates latent manganese deficiency in maize plants.